Teachers’ Well-Being, Emotions, and Motivation During Emergency Remote Teaching Due to COVID-19 - Panadero, Ernesto; Fraile, Juan; Pinedo, Leire; Rodríguez-Hernández, Carlos; Balerdi, Eneko; Díez, Fernando (Frontiers in Psychology, 2022)
This study explores the effects of the shift to emergency remote teaching (ERT) on teachers’ levels of wellbeing, emotions, and motivation. A total of 936 Spanish teachers from all educational levels participated in this nationwide survey. Four aspects were explored: (1) instructional adaptation to ERT; (2) wellbeing changes and the main challenges in this regard; (3) changes in emotions; and (4) changes in motivation and the main factors. Importantly, we explored a number of teachers’ characteristics (e.g. gender, age) in the three last aspects. Our results show that teachers felt the impact of ERT in three areas, but also that some teachers suffered to a greater extent. Female teachers, teachers with students from low socioeconomic status (SES), in public schools, and primary and secondary teachers as the most affected groups. This indicates that the impact was different and some populations of teachers are more at risk of suffering burnout if we need to go back to ERT.